The Influence of Air‐Sea Fluxes on Atmospheric Aerosols During the Summer Monsoon Over the Tropical Indian Ocean. Issue 1 (9th January 2018) - Zavarsky, Alex; Booge, Dennis; Fiehn, Alina; Krüger, Kirstin; Atlas, Elliot; Marandino, Christa
Abstract: During the summer monsoon, the western tropical Indian Ocean is predicted to be a hot spot for dimethylsulfide emissions, the major marine sulfur source to the atmosphere, and an important aerosol precursor. Other aerosol relevant fluxes, such as isoprene and sea spray, should also be enhanced, due to the steady strong winds during the monsoon. Marine air masses dominate the area during the summer monsoon, excluding the influence of continentally derived pollutants. During the SO234‐2/235 cruise in the western tropical Indian Ocean from July to August 2014, directly measured eddy covariance DMS fluxes confirm that the area is a large source of sulfur to the atmosphere (cruise average 9.1 μmol m −2 d −1 ). The directly measured fluxes, as well as computed isoprene and sea spray fluxes, were combined with FLEXPART backward and forward trajectories to track the emissions in space and time. The fluxes show a significant positive correlation with aerosol data from the Terra and Suomi‐NPP satellites, indicating a local influence of marine emissions on atmospheric aerosol numbers. Plain Language Summary: The air‐sea flux trace gases and their transformation to aerosols and cloud condensation nuclei may be fundamental to cloud formation in the marine environment. Clouds and aerosol have an important influence on the radiative balance of the earth. The local coupling of air‐sea fluxes and the formation of aerosols and clouds over the ocean is still highly uncertain. This study combines directly measured air‐sea fluxes with satellite aerosol remote sensing. It is a novel, interdisciplinary approach where results from air‐sea gas transfer are combined with atmospheric chemistry satellite remote sensing using meteorological transport models. Our results strongly support a local influence of marine‐derived aerosol precursors on cloud condensation nuclei and aerosol optical depth above the tropical Indian Ocean. Key Points: Linkage of sulfur source gases and remotely sensed aerosol numbers Western tropical Indian Ocean DMS hot spot confirmed First eddy covariance measurements of DMS in the Western Tropical Indian Ocean